Students' Evaluations of University Teaching: Balance and Perspectives of their Agenda - Edna Luna Serrano; Alma Delia Torquemada González (Universidad Autónoma de Baja California, 2008)
This work has the purpose of critically evaluate the findings of literature in relation to the administration and use of the teacher's evaluation instruments in which the students can qualify the efficiency of teaching. The discussion may help orient the use of this kind of instruments within the frame of an evaluation system to improve teaching at college level. The work includes six sections: the discussion context; evaluation of teacher's efficacy; methodological aspects, i.e, reliability and validity; the use of instruments and the improvement of teacher's efficacy. It is concluded that evaluative instruments are useful as a system's information source with use and administration requirements derived from research findings as well as empirical data. Also, establishing the link between evaluation results and the design of new modalities of teacher's formation is discussed.